Reconciliation from an African perspective: an alternative view - Zulu, E. (Old Testament essays, 1998)
The article looks at how a positive view on ancestors can impact positively on reconciliation in South Africa. This is owing to its strong emphasis on ubuntu communality, which always seeks for peace and harmony in the community. This is similar to the Old Testament perspective on reordering the community in accordance with the norms of God presupposed in the act of atonement. Sin is covered or wiped away to provide a scenario conductive to peace and harmony.